A heparan sulfate-targeted conditionally replicative adenovirus, Ad5.pk7-Δ24, for the treatment of advanced breast cancer - Ranki, T (2006)
Conditionally replicating adenoviruses (CRAds) that replicate in tumor but less in normal cells are promising anticancer agents. A major determinant of their potency is their capacity for infecting target cells. The primary receptor for serotype 5 adenovirus (Ad5), the most widely used serotype in gene therapy, is the coxsackie-adenovirus receptor (CAR). CAR is expressed variably and often at low levels in various tumor types including advanced breast cancer. We generated a novel p16/retinoblastoma pathway-dependent CRAd, Ad5.pK7-Δ24, with a polylysine motif in the fiber C-terminus, enabling CAR-independent binding to heparan sulfate proteoglycans (HSPG). Ad5.pK7-Δ24 mediated effective oncolysis of all breast cancer cell lines tested. Further, we utilized noninvasive, fluorescent imaging for analysis of antitumor efficacy in an orthotopic model of advanced hormone refractory breast cancer. A therapeutic benefit was seen following both intratumoral and intravenous delivery. Murine biodistribution similar to Ad5, proven safe in trials, suggests feasibility of clinical safety testing. Interestingly, upregulation of CAR was seen in low-CAR M4A4-LM3 breast cancer cells in vivo, which resulted in better than expected efficacy also with an isogenic CRAd with an unmodified capsid. These results suggest utility of Ad5.pK7-Δ24 and the orthotopic model for further translational studies.